(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The present study evaluates the pesticidal activity of botanical extracts from Holy Basil (Ocimumbasilicum), Neem (Azadirachta indica), Garlic (Allium sativum), and Onion (Allium cepa) against Scale (Phereoceauterella), Aphid (Aphid citricola), and Mealy Bugs. The extracts were tested at different concentrations (10, 20, 30, 40, and 50 g/l). Data on larvae and adult mortality, emergence, and repellence were collected. Additionally, fuzzy logic was applied to assess the effectiveness of botanical pesticides. Results demonstrated varying effects based on plant species and dose rate. Neem exhibited the highest larvicidal effects, while Holy Basil and Garlic demonstrated both strong repellent and anti-feeding effects. Fuzzy logic provided defuzzified values for Mealy Bug Reduction, offering a more precise evaluation of the botanical pesticides’ efficacy.